A neuroethics framework for the Australian Brain Initiative - Carter, A; Richards, LJ; Apthorp, D; Levy, NL (Elsevier, 2019)
Neuroethics is central to the Australian Brain Initiative's aim to sustain a thriving and responsible neurotechnology industry. Diverse and inclusive community and stakeholder engagement and a trans-disciplinary approach to neuroethics will be key to the success of the Australian Brain Initiative.